2023
DOI: 10.1101/2023.10.06.561306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tRNA-specific function for tRNA methyltransferase Trm10 is associated with a new tRNA quality control mechanism inSaccharomyces cerevisiae

Isobel E. Bowles,
Jane E. Jackman

Abstract: InSaccharomyces cerevisiaea single homolog of the tRNA methyltransferase Trm10 performs m1G9 modification on 13 different tRNAs. Here we provide evidence that the m1G9 modification catalyzed byS. cerevisiaeTrm10 plays a biologically important role for one of these tRNA substrates, tRNATrp. Overexpression of tRNATrp(and not any of 38 other elongator tRNAs) rescues growth hypersensitivity of thetrm10Δstrain in the presence of the antitumor drug 5-fluorouracil (5FU). Mature tRNATrpis depleted intrm10Δcells, and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Interestingly, the trm10Δ strain exhibited the most severe growth defect when grown in 5FU compared to single deletion strains of other tRNA and rRNA modification genes (Figure ). Although a general negative effect on tRNA structure was implied by the original observations, subsequent studies in our lab have revealed that a single tRNA (tRNA Trp ) is responsible for the observed hypersensitivity to 5FU in the absence of Trm10 modification due to the extremely depleted levels of tRNA Trp , but not other Trm10 substrate tRNAs, in trm10Δ cells . We also showed that tRNA Trp abundance is already significantly decreased in trm10Δ cells even in the absence of 5FU, where viability is not impacted .…”
Section: Biological Function Of the Trm10 Modification In S Cerevisiaementioning
confidence: 48%
See 3 more Smart Citations
“…Interestingly, the trm10Δ strain exhibited the most severe growth defect when grown in 5FU compared to single deletion strains of other tRNA and rRNA modification genes (Figure ). Although a general negative effect on tRNA structure was implied by the original observations, subsequent studies in our lab have revealed that a single tRNA (tRNA Trp ) is responsible for the observed hypersensitivity to 5FU in the absence of Trm10 modification due to the extremely depleted levels of tRNA Trp , but not other Trm10 substrate tRNAs, in trm10Δ cells . We also showed that tRNA Trp abundance is already significantly decreased in trm10Δ cells even in the absence of 5FU, where viability is not impacted .…”
Section: Biological Function Of the Trm10 Modification In S Cerevisiaementioning
confidence: 48%
“…Although a general negative effect on tRNA structure was implied by the original observations, subsequent studies in our lab have revealed that a single tRNA (tRNA Trp ) is responsible for the observed hypersensitivity to 5FU in the absence of Trm10 modification due to the extremely depleted levels of tRNA Trp , but not other Trm10 substrate tRNAs, in trm10Δ cells . We also showed that tRNA Trp abundance is already significantly decreased in trm10Δ cells even in the absence of 5FU, where viability is not impacted . Thus, the impact of the Trm10 modification even in yeast is biologically significant despite the lack of an obvious growth defect in trm10Δ cells grown under standard laboratory conditions.…”
Section: Biological Function Of the Trm10 Modification In S Cerevisiaementioning
confidence: 53%
See 2 more Smart Citations